Pragmatic Failure in the Subtitles of Moonlight Movie - Mahniza, Melda; Lubis, Syahron; Mono, Umar; Hanafiah, Ridwan (Yayasan Visi Intan Permata, 2020)
This paper aims to find out the types of pragmatic failures that can lead to incorrect understanding of meaning by the audience. Pragmatic failure in translation consists of two failures, namely: pragmalinguistic failure and sociopragmatic failure. Pragmalinguistic failures in translation are analyzed using speech act theory proposed by Searle and deixis theory proposed by Levinson. Sociopragmatic failures in translation are analyzed using the principle of cooperation theory proposed by Grice and the principle of politeness theory proposed by Brown and Levinson. The research method used is descriptive qualitative. One hundred seventy-six pragmatic failures are found in the subtitles of Moonlight movie, which is divided into one hundred thirty-six pragmalinguistic failures and forty sociopragmatic failures. Pragmalinguistic failures that occur are the failures to transfer speech acts and deixis of oral speech into subtitles. Sociopragmatic failures that occur are the failures to transfer principle of cooperation of oral speech into subtitles.